Vascular brain-derived neurotrophic factor pathway in rats with adjuvant-induced arthritis: Effect of anti-rheumatic drugs. (July 2018) - Pedard, Martin; Quirié, Aurore; Totoson, Perle; Verhoeven, Frank; Garnier, Philippe; Tessier, Anne; Demougeot, Céline; Marie, Christine
Abstract: Background and aims: In rheumatoid arthritis, the control of both disease activity and standard cardiovascular (CV) risk factors is expected to attenuate the increased CV risk. Evidence that brain-derived neurotrophic factor (BDNF) plays a role in vascular biology led us to investigate the vascular BDNF pathway in arthritis rats as well as the interaction between endothelial nitric oxide (NO) and BDNF production. Methods: The aortic BDNF pathway was studied in rats with adjuvant-induced arthritis, (AIA) using Western blot and immunohistochemical analysis. Control of arthritis score was achieved by administration (for 3 weeks) of an equipotent dosage of etanercept, prednisolone, methotrexate, celecoxib or diclofenac. Aortas were exposed to an NO donor or an NO synthase inhibitor and vasoreactivity experiments were performed using LM22A-4 as a TrkB agonist. Results: Vascular BDNF and full length tropomyosin-related kinase B receptor (TrkB-FL) were higher in AIA than in control rats. These changes coincided with decreased endothelial immunoreactivity in BDNF and pTrkB tyr816 and were disconnected from arthritis score. Among anti-rheumatic drugs, only prednisolone and methotrexate prevented AIA-induced vascular BDNF loss. The effect of AIA on aortic BDNF levels was reversed by an NO donor and reproduced by an NOS inhibitor. Finally, LM22A-4 induced both NO-dependent vasodilation and phosphorylation of endothelial NO synthase at serine 1177. Conclusions: Our study identified changes in the BDNF/TrkB pathway as a disease activity-independent component of AIA-associated changes in endothelial phenotype. It provides new perspectives in the understanding and management of the high CV risk reported in rheumatoid arthritis. Highlights: AIA results in impaired endothelial BDNF/TrkB pathway. Vascular BDNF levels are disconnected from the severity of inflammatory symptoms in AIA. A positive loop exists between vascular BDNF and NO production in AIA.